Influence of Stakeholders' Management on Public Project Success: Evidence from Kenya - Samwel, Kipyego; Nyamiaka, Marube; Wamaitha, Lucy; Waichigo, Simon (International Journal of Entrepreneurship and Project Management, 2023)
Purpose: The purpose of this study was to examine the influence of stakeholders' management on public projects success in Kenya: Methodology: This study adopted a descriptive cross-sectional survey design. The target population was 500 staff working for the Kenya government. The study population included public work engineers, works clerks, public project managers, contractors, supervisors and community elder respondents. The research study embraced stratified random sampling method and a sample size of 150 respondents was obtained using the Yamane (1967) formula. The study further used structured questionnaires which consisted of both open-ended and closed-ended questions to collect data from the sampled population. The collected data was cleaned for clarity clearness. Coding was done on the basis of the place of the participants. The data was analyzed using excel. Data was presented using frequency tables Finding: The findings revealed that stakeholders' analysis has a positive influence on public project success. Majority of the respondents agreed that stakeholders and their roles have been successfully identified. The study concludes that stakeholders' participation had a positive impact on project success. In addition, the study suggests that proper stakeholder expectation management enhances project success. Unique Contribution to Theory, Practice and Policy: The study affirmed applications of stakeholder's theory since internal and external stakeholders power determines the success of public projects. For Practice, Public Project implementors should enhance stakeholder involvement in project decision-making. There is need for improvement in participatory planning and budgeting to enhance decision-making processes. In addition, the government should refine stakeholder management process by designing policy for stakeholder engagement. The policy, should emphasize the need to address concerns related to service timeliness, quality, and budget adherence, as well as enhancing feedback mechanisms and communication channels. Proper timeliness and quality of service delivery need to be enhanced. The government should establish mechanisms for participatory planning and budgeting, providing stakeholders with resources for active participation, addressing service timeliness and quality concerns.